2021
DOI: 10.1051/0004-6361/202039574
|View full text |Cite
|
Sign up to set email alerts
|

Holismokes

Abstract: Modeling the mass distributions of strong gravitational lenses is often necessary in order to use them as astrophysical and cosmological probes. With the large number of lens systems (≳105) expected from upcoming surveys, it is timely to explore efficient modeling approaches beyond traditional Markov chain Monte Carlo techniques that are time consuming. We train a convolutional neural network (CNN) on images of galaxy-scale lens systems to predict the five parameters of the singular isothermal ellipsoid (SIE) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…Similar to procedures used in Cañameras et al (2020Cañameras et al ( , 2021) and Schuldt et al (2021b), we model the effective lensing potential as two components, a projected lens mass component characterised by a singular isothermal ellipsoid (SIE) profile and an external shear. The axis ratio and position angle of the SIE profiles are set to values inferred from the lens surface-brightness distribution in the HSC i band.…”
Section: Training/validation Datasetmentioning
confidence: 99%
“…Similar to procedures used in Cañameras et al (2020Cañameras et al ( , 2021) and Schuldt et al (2021b), we model the effective lensing potential as two components, a projected lens mass component characterised by a singular isothermal ellipsoid (SIE) profile and an external shear. The axis ratio and position angle of the SIE profiles are set to values inferred from the lens surface-brightness distribution in the HSC i band.…”
Section: Training/validation Datasetmentioning
confidence: 99%
“…This approach accounts for the quality of HSC imaging and for the presence of artifacts and neighboring galaxies. We followed the procedure described in Schuldt et al (2021a) and C20, by modeling the lens mass distributions with Singular Isothermal Ellipsoids (SIE) using LRG redshifts and velocity dispersions from SDSS, and inferring axis ratios and position angles from the light profiles. Unlike in C20 we included external shear, and we chose lens-source pairs to produce a uniform Einstein radius distribution in the range 0.75 −2.5 , increasing the number of wide separations and of fainter (z > 0.7) lens galaxies to help recover these configurations.…”
Section: Constructing the Ground Truth Datasetmentioning
confidence: 99%
“…Machine learning can also be used to perform fast automated lens parameter inferences (see e.g. Hezaveh et al 2017;Chianese et al 2020;Schuldt et al 2021;Park et al 2021): in particular, Wagner-Carena et al (2021) showed how it is possible to carry out hierarchical inferences on lens populations with Bayesian neural networks (Charnock et al 2020). However, it is not clear whether or not these methods are able to sample the posterior probability distribution of the lens parameters in a way that is sufficiently accurate for our purposes: dedicated tests are needed.…”
Section: Application To Real Samples Of Lensesmentioning
confidence: 99%